2023
DOI: 10.3390/s23125460
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Commercial Near-Infrared Spectroscopy Measurement and Fresh Weight Diversity Modeling in Brix% for Small Tomato Fruits with Various Cultivars and Growth Conditions

Abstract: The use of non-destructive commercial near-infrared (NIR) spectroscopy to estimate Brix% was verified using all samples of cherry tomato ‘TY Chika’, currant tomato ‘Microbeads’, and the M&S or market-purchased and supplemental local source tomatoes. Additionally, the relationship between fresh weight and Brix% of all samples was examined. These tomatoes had a diversity of cultivars, growing methods, harvest timing, and production locations and varied widely from 4.0% to 14.2% for Brix% and 1.25 g to 95.84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Tsouvaltzis et al [51] reported values between 7.55 and 9.60 • Brix for cherry tomatoes grown hydroponically in rockwool slabs. In tomatoes, the TSS value increases with the color and maturity of the tomato and is mainly attributed to sugars like fructose and glucose, although it depends on the species, cultivation method and harvest time [54]. It is one of the characteristics that most affect consumer preference [55].…”
Section: Tomato Physicochemical Characterizationmentioning
confidence: 99%
“…Tsouvaltzis et al [51] reported values between 7.55 and 9.60 • Brix for cherry tomatoes grown hydroponically in rockwool slabs. In tomatoes, the TSS value increases with the color and maturity of the tomato and is mainly attributed to sugars like fructose and glucose, although it depends on the species, cultivation method and harvest time [54]. It is one of the characteristics that most affect consumer preference [55].…”
Section: Tomato Physicochemical Characterizationmentioning
confidence: 99%